2018
DOI: 10.14512/gaia.27.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Higher Education for Sustainability-Driven Entrepreneurship: The CASE Knowledge Platform

Abstract: New ways of teaching and learning as well as close cooperation between universities, business and organized civil society are needed to promote sustainable socio-economic development. In the project Competencies for a Sustainable Socio-Economic Development (CASE), members of the Alliance of Sustainable Universities in Austria have set up a knowledge platform to foster sustainability-driven entrepreneurship education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For example, there is a 3D virtual reality educational environment for entrepreneurship where users are represented as avatars, and they have the ability to move within the world in a similar manner to the real world [23]. Other examples are a tool designed to support collaborative learning within the frame of transdisciplinary projects between universities and business partners or a 10-day summer school to develop initial business plans [24,25]. Among the actions to improve graduate employability, the activities focused on transmission of skills required for employment (which includes training in entrepreneurship and self-employment) received the highest rating by 230 deans surveyed from Spanish universities [26].…”
Section: Literature Review: Employability and Entrepreneurship Compet...mentioning
confidence: 99%
“…For example, there is a 3D virtual reality educational environment for entrepreneurship where users are represented as avatars, and they have the ability to move within the world in a similar manner to the real world [23]. Other examples are a tool designed to support collaborative learning within the frame of transdisciplinary projects between universities and business partners or a 10-day summer school to develop initial business plans [24,25]. Among the actions to improve graduate employability, the activities focused on transmission of skills required for employment (which includes training in entrepreneurship and self-employment) received the highest rating by 230 deans surveyed from Spanish universities [26].…”
Section: Literature Review: Employability and Entrepreneurship Compet...mentioning
confidence: 99%
“…It is suggested that a transfer to other areas, for example the further education of employees of companies by universities, is conceivable. Ambros und Biberhofer [26], on the other hand, investigate the use of a knowledge platform for sustainability-driven entrepreneurship. Dong et al [27] present a platform for academic knowledge discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Hoeijmakers et al [55] study the Academic Collaborative Centre Limburg in relation to cross-domain knowledge transfer. ▪ ▪ ▪ ▪ Ambros [26] ▪ ▪…”
Section: Resultsmentioning
confidence: 99%
“…Herein, it is understood that a knowledgeable, skilled, committed, responsive, and responsible citizenship would have a decisive role in the realization of HESD goals [130]. Secondly, universities cater to needs of multiple stakeholders by deploying various resources [131]. Universities consume copious amounts of both renewable and non-renewable resources, thus placing significant responsibility on universities to use these resources effectively and efficiently (eco-efficiency) to fulfil the needs of present generations, without comprising the stake of future generations.…”
Section: Discussionmentioning
confidence: 99%